Performance of Subbase Layer with Geogrid Reinforcement and Zeolite-Waterglass Stabilization - Tri Harianto (Civil Engineering Journal, 2022)
Some laterite soil is an inferior material for engineering applications such as road and highway pavement, dam construction and filling material. Laterite soil stabilization is required to increase its strength for field application purposes. The potential use of zeolite and waterglass as stabilizing agents is their pozzolanic properties. This study aims to analyze the strength and bearing capacity of laterite soil stabilized by waterglass-activated zeolite and reinforced with geogrid. The soil sample was prepared with a zeolite percentage of 4, 8, 12, 16 and 20%, and waterglass as much as 2, 4 and 6% with curing times of 0, 7, 14 and 28 days. Furthermore, the physical model test was carried out in the container with the optimum composition obtained from the compressive strength (UCS) and California bearing test (CBR) test. The stabilized subbase layer with geogrid reinforcement was placed on a subgrade layer with a substandard CBR value. The results showed that the compressive strength (UCS) of stabilized soil with a curing time of 7 days was found significantly increased. The CBR value also increased with the content of additive and curing time compared to the untreated soil. The physical model test results showed that the performance of stabilized laterite soil with additives and reinforced by geogrid (ZW-geogrid) as a subbase layer provides more optimal performance in carrying the load compared to the sand-gravel mixtures material. Doi: 10.28991/CEJ-2022-08-02-05 Full Text: PDF